Fabrication of self-cleaning superhydrophobic silicone rubber insulator through laser texturing. (4th March 2021) - Patil, Deepak; Aravindan, Sivanandam; Sarathi, Ramanujam; Rao, Paruchuri Venkateswara
ABSTRACT: Silicone insulators are gaining its importance in the transmission and distribution of the power system networks. This study proposes a simple and high throughput way of fabrication of superhydrophobic silicone surfaces. The Nd:YAG nanosecond pulse laser was used to engrave six different types of structures on silicone rubber. The water contact angle (CA) and contact angle hysteresis (CAH) were measured using drop shape analyser goniometer. The self-cleaning property of the structured silicone surfaces was tested. Among six types of patterns, the structures formed through 50% scanning overlapped possess high CA (159 ± 1°) with very low CAH (3°) which is desirable for any self-cleaning surface. However, a completely irradiated silicone surface gives the highest CA (163 ± 2°) with very high CAH (61.84°). The proposed work is a vital step towards making a superhydrophobic insulator surface without the use of any coating for high voltage power system applications.